Impact of cognitive reserve on bipolar disorder: a systematic review - Matsumoto, Kazuki; Hamatani, Sayo (Frontiers in Psychiatry, 2024)
Background Cognitive reserve (CR) is a complex concept that includes premorbid IQ, years of education, and exposure to neuropsychological stimuli through work and leisure. Previous studies have suggested that CR has a positive impact on several aspects of bipolar disorder. Synthesizing the evidence to date is an important work in providing directions for future studies. The objectives of this systematic review to summary impact of CR on onsetting, relapsing bipolar episodes, buffering cognitive dysfunctions, and maintaining quality of life (QOL) in bipolar disorder. Methods Two researchers independently reviewed selected paper from three database as PubMed, PsychINFO, and Web of Science. The search keywords were “bipolar disorder” and “cognitive reserve.” The selected studies were classified as the levels of evidence according to the criteria of the Oxford Center for Evidence- Based Medicine. The results of the selected studies were summarized according to the objectives. Results Thrity six studies were included in this review. People with high CR may have fewer bipolar episodes and alleviate cognitive impairments and dysfunction. CR may keep the functional level in patients with bipolar disorder. Conclusion The results of this systematic review suggest that CR may be involved in preventing relapse of bipolar episodes and may alleviate cognitive dysfunction. However, effect on prevention of onset-risk and relapse of bipolar episodes need further investigation in prospective studies. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021270293, the protocol was registered with PROSERO (CRD42021270293).